Can the 2-hour Glucose Tolerance Test (GTT) Values Predict Metformin Failure in Women with Gestational Diabetes? [14E]. (May 2018) - Persad, Malini D.; Ou, Jennie; Bernasko, James; Garry, David; Garretto, Diana; Herrera, Kimberly
Abstract : INTRODUCTION: To determine if the GTT values have utility in predicting metformin failure in women with gestational diabetes (GDM). METHODS: A retrospective cohort study of women with GDM was conducted from 2013-2016. Included in the study were women with GDM started on metformin after a failed trial of diet therapy. Excluded from the study were women with pre-existing DM, or were started on glyburide or insulin therapy initially. Women were categorized as having adequate glycemic control on metformin (metformin success) or requiring the addition of or transition to an insulin regimen (metformin failure). Maternal demographics and GTT values were collected. The sensitivity and the specificity of the GTT values as a screening test for metformin failure were analyzed and the corresponding ROC curves were plotted to assess the performance of the test. Parametric and nonparametric statistical analyses were performed with a p value of <0.05 as significant. RESULTS: A total of 118 gestational diabetics were identified, 19 (16.1%) women failed metformin therapy. There were no significant differences in maternal demographics between groups. A ROC curve of the fasting GTT value revealed that a value of 103mg/dL was best predictive of metformin failure (AUC 0.653; p 0.04, with a sensitivity and specificity of 42% and 90% respectively. The ROC curves of the 1 hour value and 2 hour value on the GTT were not statistically significant (AUC 0.578, p 0.28; and AUC 0.579, p0.28 respectively). CONCLUSION: An elevated fasting GTT value may help predict metformin failure in women with GDM.